Looking through the glass analysis of glass vessel shards from Pinagbayanan site, San Juan, Batangas, Philippines - Cruz, Melodina Sy (Hukay, 2014)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/4366/3962